2023
DOI: 10.1097/mnm.0000000000001669
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 18F-FDG PET/computed tomography metabolic parameters in predicting sarcopenia and prognosis of treatment-naive patients with non-small cell lung cancer

Abstract: Purpose Sarcopenia tremendously impacts the quality of life but remains debatable in prognostication in treatment-naive patients with non-small cell lung cancer (NSCLC). Hence, this study aimed to find a clinically feasible approach using 18F-FDG PET/computed tomography (CT) imaging parameters and clinical characteristics to predict sarcopenia and determine independent prognostic factors. Methods Clinical characteristics and 18F-FDG PET/CT metabolic parameters, including maximum standard uptake value, metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Compared with non-sarcopenic patients, the SUVmax and SUVmean of muscle were lower in sarcopenic patients at both baseline and end-of-treatment, indicating that a reduction in glucose metabolism of muscle suggests an increased risk of sarcopenia. Even though the mechanism underlying the correlation between glucose metabolism of muscle and sarcopenia remains unclear, a similar phenomenon was observed in our previous studies [ 13 15 ]. Chu et al [ 23 ] and Besutti et al [ 24 ] found that skeletal muscle density evaluated using mean attenuation on CT was lower in sarcopenia than in non-sarcopenia.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Compared with non-sarcopenic patients, the SUVmax and SUVmean of muscle were lower in sarcopenic patients at both baseline and end-of-treatment, indicating that a reduction in glucose metabolism of muscle suggests an increased risk of sarcopenia. Even though the mechanism underlying the correlation between glucose metabolism of muscle and sarcopenia remains unclear, a similar phenomenon was observed in our previous studies [ 13 15 ]. Chu et al [ 23 ] and Besutti et al [ 24 ] found that skeletal muscle density evaluated using mean attenuation on CT was lower in sarcopenia than in non-sarcopenia.…”
Section: Discussionsupporting
confidence: 82%
“…It can offer both anatomic information derived from CT and metabolic information derived from PET, thus simultaneously obtaining the SMA and glucose metabolic parameters of muscle such as the maximum standardized uptake value (SUVmax) and mean standardized uptake value (SUVmean) at L3. Our previous studies [ 12 13 14 15 ] have confirmed that the SUVmax of muscle at L3 was lower in sarcopenic patients compared with non-sarcopenic patients before treatment, and the incidence of sarcopenia increased with declining SUVmax in patients with malignancy. Moreover, compared with SMI, the SUVmax offers a more straightforward and convenient way to predict sarcopenia [ 14 15 ].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations